Predicted ten-year risk of cardiovascular disease among patients without prior heart disease or stroke using atherosclerotic cardiovascular disease risk calculator - Taherkhani, Maryam; Ghasemi, Mohammad; Taherkhani, Adine (Researcher Bulletin of Medical Sciences, 2023)
Objective: Recognition of probable risk factors for cardiovascular disease is crucial in non-CAD patients for preventive programming. The purpose was determination of 10-year cardiovascular disease (CVD) among patients without current cardiovascular disease. Material & Methods: In this observational study that was performed as a diagnostic survey, 606 consecutive patients without current cardiovascular disease, referring to Modarres and Loghman Hospitals, Tehran, Iran in 2017 and 2018 were enrolled and ASCVD plus score determined the 10-year cardiovascular disease among them. Results: The results in this study demonstrated that mean ASCVD plus score was 13.1 ± 14.9 points. Among cases 284 (40.9%), 67 (11.1%), 154 (25.4%), and 137 (22.6%) patients were in groups 1, 2, 3, and 4, respectively. The mean risk was higher in men, diabetics, smoker, users of anti-hypertensive, statins, and aspirin, older, with higher blood pressure, and also with higher total and LDL cholesterols. Conclusion: Totally, according to the obtained results in current study, it may be concluded that 10-year risk of cardiovascular disease is relatively high among patients without current cardiovascular disease. This matter shows the importance of routine screening in such population.